Comparison of Academic Performance among Boarders and Day-Scholars - Benash Altaf; Anam Rehman; Farah Amir Ali (Aziz Fatimah Medical and Dental College, 2019)
Objective: The aim of the study is to compare the academic performance of boarders and day scholars of a medical college. Methodology: It is a retrospective comparative study conducted at a private medical college, in Faisalabad from January 2019 to September 2019. The study comprised of 214 students that included boarders and day scholars of first year and second year from medical college. Aggregate mean scores of student's result were categorized into three level for comparison between day scholars and boarders; Level I ?50%, level II 50%-70%, level III ?70%. Results: Out of 214 students, 132 (62%) were day scholars and 82 (28%) were boarders. From total of 132 day scholar students, 38 (28.8%), 84 (63.6%) and 10 (7.6%) students overall aggregates were falling in <50%, 50%-70% and >70% categories, respectively. From total of 82 boarder students, 45 (54.9%), 34 (41.5%) and 3 (3.7%) students overall aggregates were falling in <50%, 50-70 and >70% categories, respectively. Conclusion: Home environment has positive impact on academic performance.